Gone Girl as an Effort to Liberate Women’s Language Novel Gone Girl sebagai Upaya Pembebasan Bahasa Perempuan - Muhammad Rizal (MUWAZAH : jurnal kajian gender, 2020)
This paper aims to reveal feminine language narrated by the author through novel Gone Girl. The novel tells the complex story of the struggle of women in liberating their language from masculine domination. As a female author, Gillian Flynn tries to create a new narrative on women. She opens the other side of women who are rarely revealed. This author's effort is the point of the discussion. How the author practices feminine language and why she did it will be the main problem in the research. Luce Irigaray’s thoughts about feminine language is used as a tool to answer the problem. In addition, the gynocritical approach is also used to explain the issue of female author who writes about woman. This paper finds that the author of the novel experienced boredom about the portrayal of mainstream women. The author offered the anti-mainstream ways to portray women. This effort becomes a tactic for the author to liberate women from masculine domination.